A novel rare-earth high-entropy RE6MoO12 with high near-infrared reflectance as a promising inorganic "cool pigment". Issue 1 (1st January 2023) - Zheng, Junfeng; Li, Zhanqiang; Zheng, Yong; Zhao, Weijun; Tan, Fengzhi; Yang, Fan; Chen, Heng; Xue, Liyan
Abstract: Inorganic "cool pigments" exhibit excellent application potential in double-carbon strategies and energy savings. High-entropy RE6 MoO12 inorganic "cool pigments" with a disordered defect-fluorite-type structure namely, (La0.25 Y0.25 Er0.25 Ho0.25 )6 MoO12, (Nd0.25 Y0.25 Er0.25 Ho0.25 )6 MoO12 and (Tb0.25 Y0.25 Er0.25 Gd0.25 )6 MoO12, were prepared through a solid-state reaction for the first time. The optical properties, color performance and thermal insulation of these materials were characterized. These pigments exhibited a high near-infrared (NIR) reflectance of 81–98%. The average NIR reflectance of the (La0.25 Y0.25 Er0.25 Ho0.25 )6 MoO12 (97.31%) and (Nd0.25 Y0.25 Er0.25 Ho0.25 )6 MoO12 (92.50%) pigments were greater than 90%. The high-entropy RE6 MoO12 pigments possessed better chemical stabilities in acid-alkali tests than single components. In addition, the thermal conductivity of the fully dense HE-RE6 MoO12 pigments was 1.05–1.16 W m −1 K −1 at room temperature, which is approximately 40–50% lower than that of RE6 MoO12 . The designed HE-RE6 MoO12 pigments showed three colors: yellow, green and brownish red. In conclusion, the multicolored high-entropy RE6 MoO12 pigments possessed good potential for increasing NIR solar energy reflection, which can meet the needs of "cool pigments" performance upgrades.